Designing Workability of High Performance Concrete Using Rheometrical Workability Test - Szwabowski, Janusz; Golaszewski, Jacek (Communications - Scientific Letters of the University of Zilina, 2002)
In the paper the results of investigation on cement/superplasticizer compatibility in presence of air entraining agent and silica fume are presented and discussed. Investigation was carried out on standard mortars using rheometrical workability test (RWT). The research was a first step in designing HPC to be used in bridge construction. The research fully proves usefulness of RWT for estimation of compatibility of cement/SP systems and for testing of admixtures influence on rheological properties of fresh concrete.
Keywords: no keywords